The strange case of the manuscripts Pierpont M497 and Balliol College 248D in the tradition of Cicero's Lucullus - Rozzi, Stefano (Ciceroniana On Line, 2024)
Starting from some suspicions about anomalies detected in the manuscript tradition of the recentiores of Cicero’s Lucullus, this paper seeks to demonstrate the effectiveness of the spreadsheet as a tool for identifying problematic loci. Using a limited set of formulas, the problem is narrowed down to a specific range of paragraphs, followed by a targeted collation. The outcome of this analysis is the discovery that the Ball and Corv manuscripts, always placed within of a single family, are instead the result of two antigraphs belonging to different branches of the tradition of Cicero’s work. Ultimately, the system that leverages the potential of the spreadsheet proves to be effective and functional for textual criticism.